The Cognitive Skills in Interpretation of Spatial Situations in the League of Legends game. (June 2023) - Horbiński, Tymoteusz; Zagata, Krzysztof
Background: League of Legends is one of the most popularvideo games in the world. With the help of the new initiatives of the developers and publishers (Riot Games), professional international and local tournaments were established. Riot Games also took care of establishing regional leagues, such as LCK (League of Legends Champions Korea) or LEC (League of Legends European Championship). The best teams from each region have an annual chance to compete in October / November to become the esports world champions in LoL. Watching the tournaments such as world champions, as well as amateur streams on popular platforms (Twitch, YouTube) is now trending more and more. The fact that the game (especially spatial situations) can be observed by both experts (players of this game) and non-experts (players of other games or non-players at all) creates a field for scientific research. Intervention: The authors of this article wanted to establish whether or not theLeague of Legends game offers gamers with different levels of knowledge of the entire game and different range ofcognitive skills the sameinterpretation of spatial situations . Methods: The research was carried out in the form of a questionnaire (offline), in which respondents were supposed to watch five short videos presenting different situations during the game. Eighty-two respondents, divided into three groups, participated in the research. The Pearson chi-square test was used for the analysis of the differences between groups. Results and Discussion: As a consequence of the results of this study it may be concluded that gamers on different advancement level do not present the same level of interpretation of spatial situations in the game. The authors, using the scheme of knowledge of the point, lane, and area in the construction ofvideo questionnaire did not focus on the game as a whole, but wanted to highlight crucial elements of the entire game.